Cost-effectiveness of prehabilitation prior to elective surgery compared to usual preoperative care: protocol for a systematic review of economic evaluations. Issue 12 (31st December 2020) - Rombey, Tanja; Eckhardt, Helene; Quentin, Wilm
Abstract : Introduction: Preoperative functional capacity is an important predictor of postoperative outcomes. Prehabilitation aims to optimise patients' functional capacity before surgery to improve postoperative outcomes. As prolonged hospital stay and postoperative complications present an avoidable use of healthcare resources, prehabilitation might also save costs. The aim of this systematic review is to investigate the cost-effectiveness of prehabilitation programmes for patients awaiting elective surgery compared with usual preoperative care. The results will be useful to inform decisions about the implementation of prehabilitation programmes and the design of future economic evaluations of prehabilitation programmes. Methods and analysis: We will search PubMed, Embase, the Centre for Reviews and Dissemination Database, the WHO International Clinical Trials Registry Platform and ClinicalTrials.gov for full or partial economic evaluations of preoperative prehabilitation programmes conducted in any population compared with usual preoperative care. Studies will be included regardless of the type, design and perspective of the economic evaluation, and their publication year, language or status. Initial searches were performed between 30 April and 4 May 2020. Study selection, data extraction and assessment of the included studies' risk of bias and methodological quality will initially be performed by two independent reviewers and, if agreement was sufficiently high, by one reviewer. We will extract data regarding the included studies' basic characteristics, economic evaluation methods and cost-effectiveness results. A narrative synthesis will be performed. The primary endpoint will be cost-effectiveness based on cost–utility analyses. We will discuss heterogeneity between the studies and assess the risk of publication bias. The certainty of the evidence will be determined using the Grading of Recommendations, Assessment, Development and Evaluation approach. Ethics and dissemination: Ethics approval is not required as the systematic review will not involve human participants. We plan to present our findings at scientific conferences, pass them on to relevant stakeholder organisations and publish them in a peer-reviewed journal. PROSPERO registration number: CRD42020182813